Geodetic slip model of the 2011 M9.0 Tohoku earthquake - Bürgmann, Roland (2012)
The three-dimensional crustal displacement field as sampled by GPS is used to determine the coseismic slip of the 2011 M9.0 Tohoku Earthquake. We employ a spherically layered Earth structure and use a combination of onland GPS, out to ∼4000 km from the rupture, and offshore GPS, which samples the high-slip region on the interplate boundary along the Japan trench. Inversion of the displacement field for dip slip, assuming an interplate boundary of variable dip and striking 195°, yields a compact slip maximum of about 33 m located 200 km east of Sendai. The geodetic moment is 4.06 × 10^22 N m, corresponding to Mw = 9.0. The area of maximum slip is concentrated at a depth of about 10 km, is updip of the rupture areas of the M≳7 Miyagi-oki earthquakes of 1933, 1936, 1937, and 1978, and roughly coincides with the rupture area of the M7.1 1981 Miyagi-oki earthquake. The overlap of the 2011 slip area with several preceding ruptures suggests that the same asperities may rupture repeatedly with M≳7 events within several decades of one another.